2019
DOI: 10.1136/vetreco-2017-000251
|View full text |Cite
|
Sign up to set email alerts
|

Urinary calcium assessment and its relation with age, sex and Encephalitozoon cuniculi serological status in otherwise healthy pet rabbits

Abstract: BackgroundUrinary calcium excretion by rabbits is set proportionately higher than that of other species, giving the rabbit urine its characteristic cloudy appearance. During pregnancy, lactation and growth, or when metabolic disorders interfere in the renal excretion of calcium, it is reported that less calcium is excreted and the urine appears clear. The quantification of the calcium concentration in the urine of rabbits may be of importance in the management of diseases that affect calcium metabolism, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies identified E. cuniculi by PCR in an AIDS patient (genotype III) [ 35 ], Crohn’s disease patients [ 39 ], water samples from Madrid (genotypes I and III) [ 38 ], the Iberian lynx ( Lynx pardinus ) in southern Spain [ 40 ], and captive chimpanzees ( Pan troglodytes ) in Madrid (genotype I) [ 41 ], demonstrating the presence of this species in mainland Spain. Furthermore, other studies reported cases in domestic rabbits in Spain using indirect immunofluorescence testing [ 36 ], histopathological analysis [ 42 , 43 ], or serological analysis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, the molecular characterization of E. cuniculi in rabbits from Spain has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified E. cuniculi by PCR in an AIDS patient (genotype III) [ 35 ], Crohn’s disease patients [ 39 ], water samples from Madrid (genotypes I and III) [ 38 ], the Iberian lynx ( Lynx pardinus ) in southern Spain [ 40 ], and captive chimpanzees ( Pan troglodytes ) in Madrid (genotype I) [ 41 ], demonstrating the presence of this species in mainland Spain. Furthermore, other studies reported cases in domestic rabbits in Spain using indirect immunofluorescence testing [ 36 ], histopathological analysis [ 42 , 43 ], or serological analysis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, the molecular characterization of E. cuniculi in rabbits from Spain has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In all sterilized rabbits and in entire females, urine samples were collected by manual expression of the urinary bladder on a surface cleaned without quaternary ammonium disinfectants or chlorhexidine, as recommended by the dipstick manufacturer. In entire male rabbits, the urine samples were obtained via ultrasound‐guided cystocentesis because previous observations indicate that urinalysis of samples from unneutered male rabbits obtained by methods other than cystocentesis can be inaccurate 23 . It has been previously shown that urinalysis results from urine samples obtained by cystocentesis do not differ from those obtained by manual expression of the urinary bladder in rabbits 23 .…”
Section: Methodsmentioning
confidence: 99%
“…In entire male rabbits, the urine samples were obtained via ultrasound‐guided cystocentesis because previous observations indicate that urinalysis of samples from unneutered male rabbits obtained by methods other than cystocentesis can be inaccurate 23 . It has been previously shown that urinalysis results from urine samples obtained by cystocentesis do not differ from those obtained by manual expression of the urinary bladder in rabbits 23 . A urine volume of 0.5 ml was considered sufficient to perform a complete urinalysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations